2021
DOI: 10.33884/jab.v5i2.4466
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Jenjang Pendidikan Dan Skala Usaha Terhadap Penggunaan Informasi Akuntansi Pada Umkm Kecamatan Pamulang Kota Tangerang Selatan

Abstract: One of the big problems of SMEs that happen in Indonesia is manual bookkeeping. Therefore, it leads to difficulty in calculating turnover, gross profit, and net profit, inhibiting SMEs from growing and scaling up the business. This study aims to observe and determine whether there is an influence of Education Level and Business Scale on the Use of Accounting Information in SMEs in Pamulang District Tangerang Selatan. The tests carried out show that the education level variable significantly affects and the bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
2
0
3
Order By: Relevance
“…(Afifah & Rachman, 2022) Educational level refers to a certain stage of education that is decided by the student's level of development, the goals they aim to reach, and the skills they need to develop. (Dewi & Purwatiningsih, 2021) found that having a high level of education strongly influences how one uses financial information. The degree of education of MSMEs influences how they use and use accounting information, according to earlier study.…”
Section: Relationship Between Business Scale and The Use Of Accountin...mentioning
confidence: 99%
See 1 more Smart Citation
“…(Afifah & Rachman, 2022) Educational level refers to a certain stage of education that is decided by the student's level of development, the goals they aim to reach, and the skills they need to develop. (Dewi & Purwatiningsih, 2021) found that having a high level of education strongly influences how one uses financial information. The degree of education of MSMEs influences how they use and use accounting information, according to earlier study.…”
Section: Relationship Between Business Scale and The Use Of Accountin...mentioning
confidence: 99%
“…According to the research results of (Efriyenty, 2020), The age of the company has a significanty impact on the use of accounting information.. The research conducted by (Dewi & Purwatiningsih, 2021) It was found that the level of education of the individual has a significant impact on the use of accountancy information.…”
Section: Relationship Between Business Scale Business Age and Educati...mentioning
confidence: 99%
“…Skala usaha merupakan kemampuan suatu perusahaan dalam mengelola usahanya berdasarkan jumlah karyawan dan pendapatan perusahaan dalam kurun waktu tertentu. Semakin besar skala bisnisnya, semakin kompleks proses bisnisnya, dan kebutuhan akuntansi untuk kelangsungan bisnis semakin meningkat, sehingga informasi akuntansi dapat digunakan sebagai alat bantu pengambilan keputusan manajemen (Dewi dan Purwatiningsih, 2021). Ukuran perusahaan menggambarkan besar kecilnya perusahaan.…”
Section: Pendahuluanunclassified
“…Uji t (Korelasi Parsial) Uji t merupakan uji yang digunakan untuk mengetahui seberapa besar pengaruh masing-masing variabel bebas (X) terhadap variabel terikat (Y). Hasil nilai signifikansi < dari 0,05 artinya memiliki pengaruh secara parsial, jika nilai signifikansi > dari 0,05 artinya tidak memiliki pengaruh secara parsial (Dewi, 2021). c. Koefisien Determinasi Koefisien determinasi merupakan uji yang digunakan untuk mengetahui seberapa besar pengaruh yang ditimbulkan dari seluruh variabel bebas (X) terhadap variabel terikat (Y) (Saputra & Zulmaulida, 2020).…”
Section: Uji Hipotesisunclassified